TRANSFORMASI TEKNOLOGI, PENGEMBANGAN ALAT BANTU MESIN PRESS SEALER UNTUK OPTIMALISASI PENGEMASAN PRODUK UMKM KERIPIK UBI DAN PISANG - Surti Zahra; Iis Nurasiah; Juhandi Juhandi; Sardan Sardan; Muhammad Andrianto; Yogi Saputa (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Product packaging is an important aspect for Micro, Small and Medium Enterprises (MSMEs) to increase the competitiveness and attractiveness of products in the market. In Terumbu Village, Serang City, Banten, the majority of people work as farmers and have MSME businesses, one of which is the production of sweet potato chips and bananas. Currently, some MSME players still use traditional tools in the product packaging process, which causes packaging to be less neat and sometimes unhygienic. This study aims to evaluate the effect of using plastic press machines on the quality and efficiency of packaging MSME products in Reef Villages. The methods used are observation, interviews, and literature studies to collect data on existing packaging processes and understand the needs and challenges faced by MSMEs. The results showed that the use of plastic press machines provides significant benefits for the packaging of MSME products. The use of a plastic press allows product packaging to take place faster, neater, and more hygienic compared to the manual method of using candles. Neat and professional packaging increases the attractiveness of the product in the eyes of consumers